Development of Feeding System for Muscovy Duck - Khalil .; J.A. Gartner; D. Little (Buletin Ilmu Makanan Ternak, 1990)
The objective of this study was to develop a feeding strategy for muscovy ducks utilizing fibrous feeds for potential integration with fish culture in rainfed area of Northeast Thailand. An experiment was designed to study the effect of four different feeding strategies based on plane of nutrition of the starter and grower diets for a 12 week growing period. Strategy 1 (S1) was to feed duck with high nutritional plane of starter diet for 6 weeks, subsequently followed by high nutritional plane of grower diet for another 6 weeks. S2 and S3 were high nutritional plane of starter diets for 6 and 3 weeks, and subsequently followed by low nutritional plane of grower diet for 6 dan 9 weeks, respectively. S4 was low nutritional plane of starter diets for 6 weeks and subsequently followed by low nutritional plane of grower diet for another 6 weeks. Muscovy ducks were able to utilize efficiently a fibrous diets with low protein and energy. It is necessary to feed a high plane of nutrition for 3 weeks of a duck's starter period prior to feeding fibrous diet in order to attain good growth.